Socio-economic status of lesser known Kathani cattle owners in Vidarbha region of eastern Maharashtra state - RL Bhagat; NL Phadke; Vinod Potdar; Marimuthu Swaminathan; PK Singh; MS Tantia (Journal of Livestock Biodiversity, 2025)
Data collected on 9,750 Kathani cattle owners from 118 randomly selected villages distributed in thirteen tehsils of three districts (Chandrapur, Gadchiroli and Gondia) from Vidarbha region of eastern Maharashtra collected during December 2017 to May 2018 were analyzed for studying socio-economic aspects. As Kathani cattle is not yet registered breed at national level consequently these animals were considered under Non-Descript category in animal census. The study results indicated that total Kathani cattle population was observed to be 68,146 in the survey area of which 84.37 per cent were large ruminants, while 15.63 per cent small ruminants. In large ruminants the fraction of Kathani population was 89.95 per cent. All farmers under survey were found keeping 51,720 Kathani animals leading to an average herd size of 5.30 per family. Nearly 85.81 per cent respondents were involved in agriculture farming, percentage of agriculture labours was 14.04 and a small fraction of less than one per cent (0.15) engaged in business like repairing, barber, cow Rakhwaldari, Chaprashi, tailor, goat keeping etc. In survey areas 75.10 per cent farmers were landholders owning average land 3.42±0.05 acres, however percentage of landless was 24.90. Animal status-wise it was noticed that 62.53 per cent animals were breed-able, 23.19 per cent young stock (1 to 3years age), while 14.27 per cent calves below 1 year. The utility of animals revealed that 89.14 per cent Kathani cattle owners were mainly used these animals for agricultural operations and nearly 10.48 per cent of farmers considered these animals fit for milk production, mainly to meet home consumption needs. The study further showed that 85.70 per cent owners narrated specific benefits they were gained from maintaining these cattle and the benefits were broadly classified as for religious purpose, quality manure for agriculture land, fulfils households need as and when arises by animal sale, milk for home consumption, bullocks for draft purpose, help to maintain clean environment, more disease resistance and no frequent illness, very good draft-ability of agriculture work, less requirement of feed and fodder and minimum maintenance cost. Along with benefits achieved through maintaining Kathani cattle the owners narrated expectations for betterment of these animals in future, these expectations were better market facility for milk and animal sale, sufficient feed and fodder, good quality bull and semen availability for breeding their animals, more availability of grazing land in forest areas, some type of incentives like vaccination, deworming, animal health care, supply of mineral mixture, help for animal shed constructions, health supplements to the animals etc.